Improved‐Q inductors using airbridges for GaN phase shifters. Issue 6 (June 2015) - Ross, Tyler; Hettak, Khelifa; Cormier, Gabriel; Wight, Jim S.
ABSTRACT: This article proposes the use of inductors suspended in air to increase the self‐resonance frequency and quality factor of inductors used in high‐frequency lumped MMIC designs. This technique is compatible with MMIC processes having airbridges with no additional processing, which are quite common in III–V technologies. A measured example demonstrates lower dispersion, an increase in quality factor of 18% and a 4% increase in the self‐resonance frequency of a 1 nH inductor in a GaN MMIC process with a 1 μm airbridge. As a further demonstration, the technique is applied in the design of a high‐power 0°/45° switched phase shifter designed around 25 GHz. This phase shifter MMIC uses GaN HEMTs which have a peak ft of 27 GHz and offers wideband performance. © 2015 Wiley Periodicals, Inc. Microwave Opt Technol Lett 57:1455–1459, 2015